Evaluation of the Petrophysical Properties of Yamama Formation in Ratawi oil Field, South of Iraq - E. Nasser, Medhat; Hassan AL-Sharaa, Ghazi; Sh. ALhakeem, Naseem (Iraqi Journal of Science, 2023)
This paper contains studying of the Evaluation for the Petrophysical Properties ofYamama Formation in Ratawi Field which occurs in about 70 km to the west ofBasrah city in Mesopotamia zone (Zubair subzone). The study includes apetrophysical evaluation and (3 Dimensions) geological model for each unitespecially the three hydrocarbon units comprising the Yamama Formation in (5)boreholes which are Rt-3, Rt-4, Rt-5, Rt-6 and Rt-7 distributed on the crest andflanks of the Ratawi structure that are carried out in the present study. Theformation's boundaries were determined using well logs, available core intervals andby Petrophysical data and it is found that it can be subdivided into three mainreservoir units (YR-A, YR-B and YR-C), separated by two permeability barrierunits, YB-1, and YB-2.